AN APPLICATION OF FUZZY PARTICLE SWARM OPTIMIZATION FOR CUSTOMER ANALYSIS - Nguyễn Thị Như Na (Tạp chí Khoa học Đại học Đà Lạt)
This article presents the application of the Fuzzy Particle Swarm Optimization algorithm for analyzing customer needs. Applying Fuzzy Particle Swarm Optimization algorithm to the problem of a US medical device supplier wanting to analyze the needs of 500 hospitals, in the region in terms of, medical equipment and supplies, the needs analysis assisted. The supplier offering the most suitable business strategies for each hospital to achieve higher revenues.